Proses Pengembangbiakan Bakteri Kultur Tercampur Untuk Pengolahan Limbah Cair Produksi Minyak Sawit - Zafira, Nesa; Andrio, David; Veronika, Nina (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Palm Oil Mill Effluent (POME) has total COD concentration 35.000 mg/L. In terms to treat the high strength organic wastewater, sludge from POME treatment plant which contained mixed cultures bacteria can be used as inoculum. This process was called seeding that has function to increase growth phase of the bacterial biomass by using glucose technical grade as substrate for bacteria to consumed. This study was conducted in Circulating Bed Reactor (CBR) as batch reactor with working volume of 25L, ratio of glucose : inoculum = 50% : 50%. This research aimed to study the effect of the glucose degradation in order to increase the bacterial biomass. This process was done in five days with removal rate of soluble COD and growth rate of VSS that has amount of 2.278 mg/L/day and 1.116 mg/L/day, respectively. Meanwhile the removal efficiency of soluble COD was 28,57% and growth efficiency of VSS was 67,4%. Keywords: Palm oil mill effluent, Circulating bed reactor, Seeding process, Mixed cultures bacteria, glucose, soluble COD, VSS